CYBERBULLING AND REAL REALITY - Marzano, Gilberto; Lubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There are various risks tied to cyberspace. Some of them are social risks because they are cultural risks, being related to new forms of relationships and interactions among people. In the last decade, toxic evils like cyberbullying and other malicious cyber violence are growing, and the search of antidotes is becoming a common concern for governments, educational authorities, teachers, parents and children alike. The available data shows clear evidence that the number of persons affected by cyber violence is increasing (Shariff e Churchill, 2009; U.S. Department of Education, 2011; Dilmac, 2012; Catalano, 2012): a Google search of the word “cyberbullying” finds more the 11 million of items. Despite the popularity of the word, there is a limited knowledge of this issue and many of the first conceptual formulations about it continue to be spread in literature, such as that the characteristics of bullies who act face-to-face and those who do so in cyberspace are very different. The paper analyzes the classic model of cyberbullying behavior, as described in literature, introducing a new element to be considered. It is that, especially for young people, Web and physical world are more and more becoming a whole: virtual-web and real reality are a continuum that we could define as an e-real-reality. Analyzing two of the most known cases of cyberbullying and considering some other evidences emerged by recent researches, we are theoretically convinced that a better understanding of this element could lead to the development of more effective strategies for combating cyberbullying.